Economic Determinants of Protest Behavior of the Russian Population - Денис Олегович Стребков (Journal of Economic Sociology, 2010)
The paper is devoted to the studding of mass protest of Russian population: to the search for the economic changes that have the strongest links to the protest activity and disclosing of the concrete types of correlation between them.  It is shown that the mass protest has two independent components: strikes at the enterprises from the one hand and public actions of protest including meetings, manifestations, picketing and starvations. During the three years (1996-98 ) there was an exponential correlation between the number of strikes participants and the temps of arrears growth. The number of public strikes participants does not correlate with any of the economic variable. There were also revealed four factors that were independent characteristics of social behavior: conform behavior, passive dissatisfaction, public protest and strike protest.